Dunia Sukarelawan Remaja: Frekuensi Aktivitas Kerelawanan dan Psychological Well-Being Sukarelawan Remaja di Bali - Ni Putu Natalya; Yohanes Kartika Herdiyanto (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2016)
Voluntary activities are positive activities to facilitating the youth energy for psychologically health and have positive identity formation and predictors of psychological well-being (Bruns, 2012). These are appeal activities for youth. In fact, so much youth activity made a lot of volunteers who have been trained doesn?t participate in voluntary activities. However, there are some youth volunteers who have many years of volunteering spend some time to doing voluntary activities (Dewiyanti, 26 Oktober 2014). The amount of contributed time to voluntary activities may be related with self-acceptance, personal growth, positive relationship with others, environmental mastery, autonomy and purpose of life, there are part of psychological well-being. Purpose of this research are to know the correlation between the frequency of voluntary activities and psychological well-being and factors of that results in youth volunteers in Bali, also want to know the meaning of voluntary activities for youth volunteers in Bali.Methods of this research is quantitative combination in compelementary method (n = 398; age 13-22 years) and qualitative (n = 19 of 398). Spearman's test of quantitative data showed no significant correlation between the frequency of voluntary activities and psychological well-being of youth volunteers in Bali (Men rxy= 0,022;P=0,844, Women rxy= 0,033;P=0,556) because of early adolescence and frequency of voluntary activities can?t describe quality of voluntary activities. The meaning of voluntary activities by youth volunteer in Bali are a social identity, role and self esteem. Results of this research about factors of psychological well-being youth volunteer such as ages, quality voluntary activities, non-voluntary activities and meaning of voluntary activities will be discussed later. Keywords: volunteer, youth, psychological well-being